Dinamika Pengawasan Partisipatif dalam Pemilu 2024: Studi Implementasi Kebijakan Perbawaslu No. 2 Tahun 2023 di Kantor Bawaslu Kota Kupang - Sisilia Olivera Mambo; Hendrikus Likusina Kaha; Indriyati; Yohanes Kornelius Ethelber (LPPM STISIP IMAM BONJOL, 2025)
Community participatory supervision has been carried out through the implementation of the Perbawaslu No. 2 of 2023 policy by the Kupang City Bawaslu which aims to increase public participation in election and/or election supervision. The problem in this writing is that there are still allegations of violations in the election, there is a lack of understanding from the public, including election participants, related to participatory supervision and limited internal human resources. The method used in this writing is qualitative descriptive by describing the policy implementation process based on Edward III's theory. The results of the discussion in this writing show that the implementation of the Perbawaslu No. 2 of 2023 policy has been carried out well, but there are still some obstacles, especially in terms of communication and resources.